2015
DOI: 10.1016/j.surfcoat.2014.12.004
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation performance of cold spray Ti–Al barrier coated γ-TiAl intermetallic substrates

Abstract: Four blends of Al powder containing different amounts of Ti were deposited onto Ti-46Al-7Nb substrates as oxidation-protection layers using low-pressure cold spray. The coating morphology and chemical composition were assessed. Optimized heat treatment in protective atmosphere was carried out in order to induce formation of intermetallic phases within the deposits. The specimens were then subjected to 950 • C exposure for 100, 250, and 500 hrs and their oxidation performance was monitored using the gravimetric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…Cizek et al 230 (3) Wang et al 97,232 deposited Fe-Al composite coatings and XRD results showed that with increasing annealing temperature, the content of the intermetallic compound increases (Figure 32a). The differential scanning calorimetry (DSC) analysis showed that Fe2Al5 was the first intermetallic phase formed upon heating at 625°C.…”
Section: Formation By Post Spray Heat Treatment Of Cold-sprayed Metalmentioning
confidence: 99%
“…Cizek et al 230 (3) Wang et al 97,232 deposited Fe-Al composite coatings and XRD results showed that with increasing annealing temperature, the content of the intermetallic compound increases (Figure 32a). The differential scanning calorimetry (DSC) analysis showed that Fe2Al5 was the first intermetallic phase formed upon heating at 625°C.…”
Section: Formation By Post Spray Heat Treatment Of Cold-sprayed Metalmentioning
confidence: 99%
“…Intermetallic compounds of the Ti-Al system have good physical and mechanical properties [22], are resistant against oxidation up to the temperatures of 800-1000 • C [23][24][25], and possess high affinity with titanium, which provides high adhesive strength of the layers. In the Ti-Al system, intermetallic compounds with different stoichiometry can be formed, but usually there are three stable intermetallides: Ti 3 Al (with an ordered hcpbased structure), TiAl (with a tetragonal L1 0 lattice, c/a = 1.02), and TiAl 3 (with tetragonal D0 22 lattice, c/a = 2.22) [2].…”
Section: Introductionmentioning
confidence: 99%
“…Again, this is resolved by cold spraying as the method allows pore-free coating formation (a significant improvement over e.g., plasma spraying). Using kinetic energy in lieu of thermal input, the method is particularly suitable for deposition of metals [8,9]. As opposed to thermal spray processes such as plasma spray or HVOF, the temperatures involved in this process remain relatively low, thereby effectively eliminating oxidation of the materials.…”
Section: Introductionmentioning
confidence: 99%